2010
DOI: 10.1590/s0102-33062010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Diatomáceas (Bacillariophyceae) em marismas no sul do Brasil

Abstract: Nas marismas do sul do Brasil a comunidade de diatomáceas é desconhecida. Este estudo visa avaliar a composição, a riqueza e a β-diversidade desta comunidade com base em amostras coletadas em cinco pontos georeferenciados, entre as coordenadas 31º59'18.60"S - 52º14'58.50"W e 32º06'49.74"S - 52º09'22.57"W, em janeiro de 2002 e março de 2008, no estuário da laguna dos Patos. Esta comunidade esteve composta por 64% de diatomáceas salobras, 24% de marinhas e 16% de dulcícolas e esteve representada por 24 famílias,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…This distribution is in agreement with that found in the literature and cited in the introduction. Silva et al 2010 found one valve of it in sediments from the Lagoa dos Patos mouth (31°59'18.60''S; 52°14'58.50''W) and in the Westerschelde estuary (The Netherlands) it occurs in silty sediments (low dynamic environments) and plankton samples (Muylaert & Sabbe, 1999 (Figures 5, 6). The valves are round to elliptical lanceolate in shape, 3.0 -9 mm long and 1.5 -3 mm wide (n ¼ 10).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This distribution is in agreement with that found in the literature and cited in the introduction. Silva et al 2010 found one valve of it in sediments from the Lagoa dos Patos mouth (31°59'18.60''S; 52°14'58.50''W) and in the Westerschelde estuary (The Netherlands) it occurs in silty sediments (low dynamic environments) and plankton samples (Muylaert & Sabbe, 1999 (Figures 5, 6). The valves are round to elliptical lanceolate in shape, 3.0 -9 mm long and 1.5 -3 mm wide (n ¼ 10).…”
Section: Resultsmentioning
confidence: 98%
“…It is herein for the first time recorded for the Rio Grande do Sul littoral at Cassino beach. Although Silva et al (2010) has cited it to Lagoa dos Patos estuary, its ocurrence in this area maybe is related to the proximity with the international port of Rio Grande.…”
Section: Final Discussionmentioning
confidence: 99%
“…Distribution: Seminavis strigosa seems to be widely distributed in brackish environments, with records in Wadi Islet and Ayun Musa oasis in the Sinai (Hustedt, 1949), Mesolonghi lagoon, western Greece (Danielidis and Mann, You et al 2008You et al 26-38 5-8 16-20 2003, and Southern Brazil (Silva et al, 2010). Amphora twenteana have been reported to freshwater environments, such as Twente Canal, Netherlands (Krammer, 2003) and Xinjiang, Northwestern China (You et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…So far, most studies concentrated on phytoplankton at Patos Lagoon [17][18][19][20][21][22][23][24], Tramandaí-Armazém Lagoon [25][26][27][28][29], and Peixe Lagoon [30][31][32][33][34]. Regarding microphytobenthic, studies were limited to salt marshes and to the Patos Lagoon estuary [35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%